Paging Dr. Patient: a diagnosis of Greek public hospitals through sentiment analysis - Andreas G. Koutoupis; Georgios L. Thanasas; Konstantina Tatsi; Theodoros V. Kounadeas; Leonidas G. Davidopoulos (International Journal of Health Care Quality Assurance, 2026)
Purpose We examine the topics and the dimensions of patient satisfaction and their implications for Greek public hospitals. Design/methodology/approach We measure patient satisfaction through the sentiment analysis of the relative ratings and commendation submitted to Google reviews for 45 Greek public hospitals. We collect the data submitted over a period of years, that is from 2013 to 2024. Findings We find that visitors of public hospitals are discouraged and disappointed mainly by the behavior of doctors, nurses and management-managerial staff as well as the building infrastructure and medical equipment that is outdated or absent. We also find a relatively underreport of reviews that denounce instances of informal payments to physicians. However, we find that doctors' scientific capabilities and knowledge significantly contribute to patient satisfaction. Our findings suggest that the Stimulus–Organism–Response (S-O-R) framework, normalization framework and institutional theories that link patient satisfaction with environmental triggers, are relative to the Greek healthcare environment as well. Originality/value Our study is driven by the relatively limited research on sentiment analysis in hospitals and particularly by invites for research on the patients' opinion as to what really is satisfactory healthcare, by contributing a specific country case study to the limited previous research in this area.